In depth investigation of Branched Amphipathic Peptide Capsules (BAPCs) for enhanced mRNA transfection efficiency - Yoon, Sungmin (Kansas State University, 2024)
This study developed new strategies to improve the delivery potential of two peptide delivery systems: branched amphiphilic peptide capsules (BAPC) and aqueous partitioning capsules (APC). The parameters investigated included transfection efficiency, endosomal escape and temporal stability. Sequence modifications to the parent sequences were investigated. Biophysical characterizations and cell biological studies were employed. Modified sequences were identified that enhanced the performance of the two capsule types.
Keywords: Nanotechnology; Gene delivery; Peptide vector; BAPC; APC